Economic analysis of seed yam production systems in Nigeria - Mignouna, Djana B.; Abdoulaye, Tahirou; Alene, A.; Aighewi, B.A.; Pelemo, O.; Manyong, Victor M.; Asiedu, Robert; Akoroda, M.O. (2013)
New seed yam systems from minisetts, minitubers and vine cuttings have been developed for yam production to supplant the traditional systems, which have proven inefficient and costly. The new techniques provide producers in tropical countries with the opportunity to minimize production costs, reduce seed yam price and promote greater seed availability. A discounted cash flow budget with a whole farm perspective was used to analyse the economic performance and risk implications of a hectare investment in the new seed yam system over time for a representative farm. Data based on realistic process costs and review of past reported studies were employed to reflect the relative economic worthiness and opportunity cost of investment and operating capital of seed yam systems in Nigeria. From the net present value (NPV) and benefit:cost ratio (BCR) analyses, the new seed yam production systems were more viable than current traditional seed yam production systems through milking of live immature plants. This raises the need to identify which among the new production techniques could be the most profitable and recommendable. Therefore, understanding the economics of seed yam production systems would not only help a significant proportion of local, regional and national stakeholders but also assist the policymakers, funding agencies and other organizations involved in yam projects and programmes.